Antioxidant Analysis of Kawa Daun (Coffea canephora) Beverage by In Vitro and In Silico Approaches - Ifwarisan Defri; Nurheni Sri Palupi; Setyanto Tri Wahyudi; Nancy Dewi Yuliana (Universitas Gadjah Mada, 2022)
In Tanah Datar Regency, West Sumatra, Indonesia, the waste of pruning coffee leaves (Coffea canephora) is utilized as a traditional beverage called